2022
DOI: 10.1109/access.2022.3167424
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study on Constant Spacing Policies for Starting Platoons at Oversaturated Intersections

Abstract: Cooperative Adaptive Cruise Control (CACC) is considered as a key potential enabler to improve driving safety and traffic efficiency. It allows for automated vehicle following using wireless communication in addition to onboard sensors. To achieve string stability in CACC platoons, constant time gap (CTG) spacing policies have prevailed in research; namely, vehicle interspacing grows with the speed. While constant distance gap (CDG) spacing policies provide superior potential to increase traffic capacity than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Over the years, policies based on temporal gaps have gained acceptance, as they are associated with greater platoon stability [14], as described in Section IX. Alternatively, some authors choose to combine them with policies based on spatial gaps, which are reported to favor the increase of capacity (e.g., [15]).…”
Section: B Car-following Rulementioning
confidence: 99%
See 2 more Smart Citations
“…Over the years, policies based on temporal gaps have gained acceptance, as they are associated with greater platoon stability [14], as described in Section IX. Alternatively, some authors choose to combine them with policies based on spatial gaps, which are reported to favor the increase of capacity (e.g., [15]).…”
Section: B Car-following Rulementioning
confidence: 99%
“…Reference [15] focused on platoons of CACC vehicles. Their aim was to show that the combination of different car-following policies (i.e., space-based and time-based) would allow maximizing traffic capacity, while preserving safety and stability.…”
Section: A Platooning Impacts On Infrastructure Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many scholars have conducted researches on unsaturated headway, The headway time distance distribution of downstream vehicles at signal intersections has been studied by Zhengdao Ding [1] , Changqiao Shao [2] , Aizeng Li [3] , Huiying Wen [4] and various fitting models have been established; Fujian Wang [5] by comparing the fitting accuracy of headway time distance distribution models, the proposed mixed headway time distance distribution model based on multi-class following behavior outperformed the Weibull distribution and lognormal distribution model; Yong Qian [6] based on the distribution law of headway time distance, a signal timing algorithm without the total lost time as a variable is discussed, and an optimal green light time control optimization method based on the headway time distance distribution and queue length is proposed; Yun Xing [7] proposed a threshold division method considering randomness, mainly including the determination of the starting point of unsaturated traffic flow calculation and the selection of division threshold; Jiaqi Li [8] and Dianhua Cheng [9] proposed a fuzzy traffic flow control scheme based on the green light time correction algorithm of headway time distance for urban intersections respectively.J Chen [10] , Xiaopeng Li [11] and Kay Massow [12] Combines the determination of headway at intersections with vehicle networking and autonomous driving.Cesme B [13] and Furth P G [14] explores a new paradigm for traffic signal control based on local actuated control but with some additional rules that create coordination mechanisms, and the simulation proved that the study had little impact on traffic delays.…”
Section: Introductionmentioning
confidence: 99%